FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WP BADAN - Hidayat, Amanda (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
Tax system in Indonesia follows self assessment system. From the self assessment system, a full trust is given to the taxpayers to register themselves at the Tax Service Office in order to calculate, deposit, and report their tax liabilities. By using self assessment, the function of the government is to facilitate so the self assessment system works properly while its implementation depends on the obedience of the taxpayers. The purpose of this research is to find out some factors which influence the obedience of the taxpayers at KPP Pratama Surabaya Gubeng.Keywords:Taxpayer Awareness Factor, Taxpayer Perception, Taxpayer Knowledge, Tax Service Quality.